Islamic empires 600-1650 - Leadbeater, Tim; Whittock , Martyn (London : Hodder Education, 2004)
This book includes all the features of the bestselling Hodder History series which is up-to-date, motivating, differentiated and flexible. It covers the rise and fall of Islamic Empires from c600 to c1650 including chapters on: The Dawn of Islam; The Empire Unfurls; Islamic Civilisation; Holy Wars; The Mughal Empire. Investigations which encourage pupils to become historical detectives and develop their enquiry skills are on fascinating topics such as: The Life of Women; Survival Skills for Rulers; Salah-ad-Din and Richard the Lionheart. As well as promoting historical skills this book integrates literacy through its guidance on extended answer questions.
Keywords: Islamic History -- non-fiction